STRATEGIES TO INCREASE THE COMPETITIVENESS OF SMALL AND MEDIUM ENTERPRISES (SME) POST COVID 19 PANDEMIC AT SENTRA WISATA KULINER (SWK) IN SURABAYA - Utari, Woro; Indrawati, Mei (STIE Pelita Nusantara Semarang, 2023)
SMEs in Indonesia continue to exist and develop despite the economic crisis that has hit this country since 1997, and have even become a lifeline for the nation's economic recovery because of their ability to make a significant contribution to PDM and employment. The existence of SMEs on social life is improving community welfare which consists of economic welfare, health welfare and educational welfare. This research uses qualitative methods, the focus of this research is on community empowerment through SMEs. In qualitative research, in-depth interviews are needed, which is one of the commonly used analytical methods. This research will attempt to interview several informants at the Culinary Tourism Center in the City of Surabaya. Research results show that with the new normal rules, SWK can be open until the evening. This was welcomed by local residents. To improve the quality of SWK, Dinkopdag is gradually making improvements ranging from service standards, re-design, to the taste of SWK products. SWK really needs attention from the City Government, not only limited to providing space but also paying attention to the sustainability of SMEs, especially in SWK which is devoid of visitors. The improvements range from implementing a single cashier, building improvements to training traders by skilled chefs.